2014
DOI: 10.1093/cid/ciu504
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Listeriosis: Clinical Characteristics and Geospatial Analysis of a 10-Year Period in Israel

Abstract: Our survey emphasizes the high rate of pregnancy-related listeriosis in Israel and shows that specific clones might account for this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 28 publications
10
72
1
Order By: Relevance
“…This is lower when compared to other countries; for example in the United States of America the incidence of neonatal listeriosis is 8.6 per 100,000 live births [15] and in Israel it is up to 25.5 per 100,000 live births [16]. Neonatal listeriosis is also rarer when compared to the more common cause M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…This is lower when compared to other countries; for example in the United States of America the incidence of neonatal listeriosis is 8.6 per 100,000 live births [15] and in Israel it is up to 25.5 per 100,000 live births [16]. Neonatal listeriosis is also rarer when compared to the more common cause M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…However, different ECs may have different pathways of infection in, or tropism for, different tissues or cells within the human body. For example, a recent study suggested "pregnancy predilection" for ECIV, as this clone clearly plays a major role in cases of listeriosis associated with pregnancy (Elinav et al, 2014).…”
Section: Adaptive Epidemic Clones (Ecs) Of L Monocytogenesmentioning
confidence: 99%
“…In recent years, epidemiology of pregnancy-related listeriosis has been investigated in several developed countries, such as England and Wales [13], France [14], United States [3], Netherlands [15], and Israel [16]. A proportion between 20.7% [5] and 43% [17] of L. monocytogenes invasive infections are related to pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Between 1984 and 2011 this indicator in France fell from 60 to 5 cases per 100000 live births, which is a decline by a factor of 12 [14]. Conversely, in the years 1998–2007 the yearly incidence of pregnancy-associated listeriosis in Israel ranged from 5.5 to 25.2 cases per 100000 births [16]. In USA, application of preventive measures (“zero tolerance”) since 1985 resulted in a 44% reduction of perinatal listeriosis, from 17.4/100000 to 8.6/100000 live births [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation